Identification of key enablers and assesment of the inter-relationship of household financial resilience in southwest Asian nations - Agrawal Reena; Saxena Charu; Thakur Pratibha (Financial Internet Quarterly)
The current research was taken up to identify and assess the key enablers of household financial resilience in Southwest Asian nations. The research technique used was Interpretive Structural Modeling. We identified twelve enablers which impact household financial resilience which we then used to try to explore financial resilience in South-West Asian households. The aim of the study was to identify the key enablers that influence urban households’ financial resilience in Southwest Asian nations, evaluate the contextual relations between the identified enablers and develop a hierarchical framework of enablers of urban households’ financial resilience in South-West Asian nations. The findings of the research disclosed that financial security was the most crucial enabler for household financial resilience followed by financial cushion at level two. However, education level and financial literacy were the foundation stones of the proposed model.